Experimental analysis of the wear behavior of hybrid metal-matrix composites of LM25Al with equal volumes of SiC + TiO2 - Elango, Gopalakrishnan (Materiali in tehnologije, 2014)
In the present work tribological behavior of aluminium alloy LM25 reinforced with SiC and TiO2 fabricated with the stir-casting process is investigated. The wear resistance and frictional properties of the hybrid metal-matrix composite were studied by performing a dry-sliding-wear test using a pin-on-disc wear tester. The experiments were conducted at a constant sliding velocity of 1.04 m/s and sliding distance of 628 m with various loads of (3, 4, 5) kg and the particle volume fraction ranging from 5-15 %. The results show that the reinforcement of the metal matrix with SiC and TiO2 reduces the wear rate at room temperature. The results also indicate that the wear of the test specimens increases with the increasing load and sliding distance. The coefficient of friction decreases with the load and increasing volume content of the reinforcement. The hardness of the hybrid-composite test specimens increases with the increasing volume fraction of the particle reinforcement of SiC and TiO2. The microstructure analysis reveals that SiC and TiO2 particulates are uniformly distributed in the matrix. The wear surfaces are examined with a scanning electron microscope which indicates abrasive wear mechanism due to the hard ceramic particles on the worn surface.
Keywords: tribološke lastnosti; drsenje; aluminijeve zlitine; aluminium alloy; kompoziti; preiskava materiala